A single-stage full bridgeless boost half-bridge AC/DC converter with bidirectional switch - Mohamad Affan Bin Mohd Noh; Mohd Rodhi Bin Sahid; Vinesh Thiruchelvam (Institute of Advanced Engineering and Science, 2021)
This paper proposes an isolated full bridgeless single stage alternating current-direct current (AC-DC) converter. The proposed converter integrates the operation of a pure bridgeless power factor correction with input boost inductor cascaded with center-tap transformer and half bridge circuit. In addition, the bidirectional switch can be driven with single control signal which further simplifies the controller circuit. It is also proved that this converter reduces the total number of components compared to some conventional circuit and semi-bridgeless circuit topologies. The circuit operation of the proposed circuit is then confirmed with the small signal model, large signal model, circuit simulation and then verified experimentally. It is designed and tested at 115 Vac, 50 Hz of input supply, and 20 Vdc output voltage with maximum output power of 100 W. In addition, the crossover distortion at the input current is minimize at high input line frequency.